Sports coaching and the law of negligence: implications for coaching practice - Partington, N. (Sports Coaching Review, 2017)
The ordinary principles of the law of negligence are applicable in the context of sport, including claims brought against volunteer and professional coaches. Adopting the perspective of the coach, this article intends to raise awareness of the emerging intersection between the law of negligence and sports coaching, by utilising an interdisciplinary analysis designed to better safeguard and reassure coaches mindful of legal liability. Detailed scrutiny of two cases concerning alleged negligent coaching, with complementary discussion of some of the ethical dilemmas facing modern coaches, reinforces the legal duty and obligation of all coaches to adopt objectively reasonable and justifiable coaching practices when interacting with athletes. Problematically, since research suggests that some coaching practice may be underpinned by "entrenched legitimacy" and "uncritical inertia", it is argued that coach education and training should place a greater emphasis on developing a coach`s awareness and understanding of the evolving legal context in which they discharge the duty of care incumbent upon them.